ANALISIS KONEKTIVITAS JARINGAN TRANSPORTASI UDARA NASIONAL - Gunawan, Gunawan; Medianto, Rully (Sekolah Tinggi Teknologi Adisutjipto, 2016)
The airport as flight network node is the starting point and the end of the movement of people/goods. The airport can also be a transit point before continuing the journey to the destination. The closure of the airport due to force majeure such as a disaster or terrorism may disrupt the national air transportation network. The effects of the closure of an airport to the national air transportation network depends on the level of connectivity of the airport. This study aimed to quantify the connectivity between two airports in the national air transportation network. Based on the connectivity data, it can be determined that appropriate mitigation strategies during an airport closure due to force majeure.